An introduction to sustainability environmental, social and personal perspectives - Martin Mulligan with Michael Buxton, Ruth Lane, Melissa Neave and Anthony Richardson (London ; New York Routledge, Taylor & Francis Group, 2018)
An Introduction to Sustainability provides students with a comprehensive overview of the key concepts and ideas which are encompassed within the growing field of sustainability.
Earlier edition: 2015.
Keywords: Sustainability